Search
Ask a question
0

x + 3y = -5, 2x - y = 18

solve using subsitution

1 Answer by Expert Tutors

Tutors, sign in to answer this question.
Kevin S. |
5.0 5.0 (4 lesson ratings) (4)
0

Using substitution, solve the first expression for x, then substitute that result in for x in the second equation: 

x = -3y - 5

2(-3y -5) - y = 18

-6y - 10 -y = 18

-7y -10 = 18

-7y = 28

y = -4

Plug this back into the first equation to find x:

x + 3(-4) = -5

x -12 = -5

x = 7

So our solution would be (7,-4)